KITAB KUNING, LITERASI, DAN PEMBENTUKAN DAYA NALAR SANTRI: EVALUASI PENDIDIKAN DI PONDOK SALAF MODERN [KITAB KUNING, LITERACY, AND THE FORMATION OF STUDENTS' REASONING POWERS: AN EVALUATION OF EDUCATION AT A MODERN SALAF BOARDING SCHOOL] - Fadillah, Muhammad Kharis; Miftahussurur, Wildan (Al-Ihtiram: Multidisciplinary Journal of Counseling and Social Research, 2025)
This study aims to examine the role of kitab kuning and literacy in shaping students’ reasoning skills through an educational evaluation of a salaf-modern Islamic boarding school. The research employed a qualitative approach with an evaluative design and was conducted at a salaf-modern pesantren. Data were collected through in-depth interviews, field observations, and document analysis, and were analyzed using descriptive-analytical techniques involving data reduction, data display, and conclusion drawing, supported by triangulation to ensure data credibility. The findings indicate that kitab kuning learning functions as an epistemic foundation for developing students’ reasoning skills by fostering systematic, analytical, and argumentative thinking. The integration of academic literacy, both oral and written, strengthens students’ abilities to articulate ideas, engage in scholarly discussions, and solve contextual religious problems. Furthermore, pesantren education demonstrates tangible social benefits through the formation of character, independence, leadership, and social contributions of students and alumni within the community. This study concludes that the salaf-modern pesantren represents a holistic and adaptive model of Islamic education oriented toward public benefit while remaining firmly rooted in the classical scholarly tradition of kitab kuning.